Globalisasi dan Dampaknya Terhadap Aksesibilitas Pengetahuan - Nuryananda, Praja Firdaus (Global and Policy Journal of International Relations, 2013)
ABSTRACTDefining globalization as internationalization and de-territorialization is shifting the role of information as the product of knowledge to be the knowledge itself. This shifting is dragging information to be a potential property of feudal who control of the access and the process. This has been marked as informational feudalism. This paper actualizes the concept of informational feudalism by giving empirical studies of Eli Lily-Madagascar and Nicotine-Pharmacy Industry in United States of America. The medicine to cure cancer had been made from rosy periwinkle came from Madagascar. Instead of being a common property, the medicine was a private property because Eli Lily had sold it to people with high price. In the USA, research studies and scientific papers were used in the campaign of using the alternative nicotine therapy, considering the harm of smoking activities. From two examples given, the remark is that information and knowledge has been becoming a new modus for feudal to take profit without educate the people.Keywords: globalization, informational feudalism, knowledge, information.DOI:https://doi.org/10.33005/jgp.v1i02.1997